2019
DOI: 10.1111/all.14027
|View full text |Cite
|
Sign up to set email alerts
|

New biological treatments for asthma and skin allergies

Abstract: Allergies are typically endemic, complex and heterogeneous diseases with a high impact at quality of life. Mechanistically, type 2 immune responses involving eosinophil and basophil granulocytes, mast cells and humoral factors such as IgE are key drivers of allergic diseases. Fighting allergic diseases knows three strategies: prevention, symptomatic and causative therapy. While remarkable progress was made in understanding molecular events in allergies as a prerequisite for effective prevention and desensitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 143 publications
(263 reference statements)
0
71
0
5
Order By: Relevance
“…Urticaria is a common skin disease, and various factors are known to be associated with the onset and/or the aggravation of urticaria. Recent development of biologics, such as omalizumab, humanized monoclonal antibody against IgE, have largely improved its treatment [38,39]. However, many patients still do not benefit from or tolerate such therapies, and the molecular mechanism of wheal formation in urticaria is poorly understood [1,2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Urticaria is a common skin disease, and various factors are known to be associated with the onset and/or the aggravation of urticaria. Recent development of biologics, such as omalizumab, humanized monoclonal antibody against IgE, have largely improved its treatment [38,39]. However, many patients still do not benefit from or tolerate such therapies, and the molecular mechanism of wheal formation in urticaria is poorly understood [1,2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Antihistamines, which are frequently used in the treatment of AD, have the effect of suppressing histamine secreted from cells, such as mast cells, and thereby suppress itching. [41,42] In addition, it has recently been reported that mast cells are also involved in the pathogenesis of AA. [43][44][45] For example, the mast cell density was significantly increased in the HF mesenchyme and surrounding perifollicular dermis of AA lesions when compared to healthy control skin.…”
Section: Ma S T Cell S In a A And Admentioning
confidence: 99%
“…IL-4 and IL-13 are key cytokines in driving the initiation and chronicity of type 2 (T2) inflammation, a dominant inflammatory pathway in AD (11,12). Dupilumab is a fully human anti-IL-4 receptor α (IL-4Rα) monoclonal antibody that blocks both IL-4-and IL-13-mediated signalling pathways (13,14). The European Medical Agency (EMA) recommends dupilumab for moderate-to-severe AD in adult and adolescents (12 years and older) patients who are candidates for systemic therapy (15).…”
Section: Introductionmentioning
confidence: 99%